SCREENING FUNGSI GINJAL SEBAGAI PERBAIKAN OUTCOME PENGOBATAN PADA PENDERITA DIABETES MELLITUS TIPE II (Studi di Wilayah Kerja Puskesmas Ngesrep) - Astri Aditya; Ari Udiyono; Lintang Dian Saaraswati; Henry Setyawan Susanto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Chronic renal failure is a progressive renal function disorder and irreversible. Diabetes is the main cause of kidney disease. Kidney damage due to chronic diabetes mellitus is common. Most of kidney disease has no symptoms, The way to find out kidney disease in people with diabetes is to do kidney examination. The purpose of this study to describe the state of kidney function in patients with type 2 diabetes mellitus in the work area of Puskesmas Ngesrep. a cross-sectional study was conducted Agustus 2017 in patients with type 2 diabetes in the work area of Puskesmas Ngesrep. The sample of this study was 77 by random sampling technique. The data were collected through interviews and measurements (blood pressure, blood sugar, BMI, blood creatinine). The results showed the proportion of patients with diabetes who have impaired kidney function totaled 88.3%. Mean of creatinine level in people with diabetes mellitus 1.4±0.8 mg/dl, mean GFR in diabetic patients 61,16±23,42 mL/min. Status of most kidney function is impaired moderate renal function with GFR 30-59mL/min (50,6%). Patients aged> 62 years (66.7%), female gender (53.7%), duration of DM> 5 years (69.2%), high fasting blood glucose (51.2%), 2 post Prandial blood glucose GD2JPP) high (51.7%), high systolic blood pressure (54.2%), high diastolic blood pressure (35.9%), high creatinine (75.0%), no oral hyperlaboremic agents and insulin (45.5%), antihypertensive (43.2%). Suggested diabetes patients control blood sugar and blood pressure levels and adjust drug consumption based on kidney function.